EFFECT OF SHED ROOF COLOUR AND BEDDING MATERIALS ON GROWTH PERFORMANCE OF CROSSBRED KIDS - H. Kumar; N. K. Sarma; J. Hussain; R. Roychoudhury (Indian Journal of Veterinary and Animal Sciences Research, 2024)
An experiment was conducted on 18 un-castrated crossbred (Beetal x Assam local) kids of 3-4 months of age to study the effect of shed roof colour and bedding materials on growth performance during winter season. Three groups of six kids in each were housed in three sheds: T1 (shed roof painted with black colour on top and white colour inside and paddy straw bedding material mixed with hydrated lime, T2 (shed roof painted with black colour on top only and paddy straw without any treatment and T3 (shed roof without any colour and bedding material). The shed T1 and T2 were covered with hessian clothes except the ventilators. The roof shed painted with black colour on top and white colour inside along with hydrated lime mixed bedding material (T1) might have provided better and comfortable micro environment both in terms of optimum temperature and hygienic condition that resulted in significantly (P